POROZUMIENIA, UMOWY ORAZ ZLECENIE USŁUG LUB INSTRUMENTÓW RYNKU PRACY NA GRUNCIE USTAWY O PROMOCJI ZATRUDNIENIA I INSTYTUCJACH RYNKU PRACY – KILKA UWAG DE LEGE FERENDA - Paluszkiewicz, Magdalena (Zeszyty Prawnicze, 2016)
THE AGREEMENTS, CONTRACTS AND COMMISSIONING OF LABOUR MARKET SERVICES OR INSTRUMENTS ON THE BASIS OF THE EMPLOYMENT PROMOTION AND LABOUR MARKET INSTITUTION ACT – A FEW COMMENTS DE LEGE FERENDA. Summary The main reason for this article is legal language inconsistency occurred in The Employment Promotion and Labour Institution Act of 20 April 2004. In connection with this statute there are reasonable doubt regarding legal nature of agreements, contracts and commissions made on its ground. The Act is abounded with various and ambiguous designations for legal action brought by labour market entities and therefore may cause serious problems in the process of application of the law. The author is of the opinion that solving of this issue may have practical importance for the state and local administration in execution of labour market assignments.